2019
DOI: 10.1007/s11192-019-03064-5
|View full text |Cite
|
Sign up to set email alerts
|

Zero impact: a large-scale study of uncitedness

Abstract: This paper presents a large-scale study of the phenomenon 'uncitedness'. A literature review indicates that uncitedness is related to at least three factors: Field, document type, and time. To explore these factors and their mutual influence further, and at much larger scale than previous studies, the paper focuses on seven subject areas (arts & humanities; social sciences; computer science; mathematics; engineering; medicine; physics & astronomy), seven document types (articles; reviews; notes; letters; confe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 40 publications
0
20
0
3
Order By: Relevance
“…Because it is very difficult to see how papers that were never cited can contribute to the growth of scientific knowledge (cf. Nicolaisen & Frandsen, 2019), it may be used as an additional indicator of quality. Although, even if a paper remains uncited for a long period, this is not necessarily a sign of its poor quality (Garfield, 1991).…”
Section: Can the Hqsi Be Improved?mentioning
confidence: 99%
“…Because it is very difficult to see how papers that were never cited can contribute to the growth of scientific knowledge (cf. Nicolaisen & Frandsen, 2019), it may be used as an additional indicator of quality. Although, even if a paper remains uncited for a long period, this is not necessarily a sign of its poor quality (Garfield, 1991).…”
Section: Can the Hqsi Be Improved?mentioning
confidence: 99%
“…However, each of these building blocks of science can be assessed differently in practice. Think of the excessive number of publications that are not cited and hardly read as a reflection of the competition for attention (Laband and Tollison 2003;Nicolaisen and Frandsen 2019;Van Dalen and Henkens 2004). And the lack of attention becomes different when your promotion or grant application depends on it, and it may change the choice of topics or a tendency to neglect national issues for scholars working in non-English countries (Van Dalen and Henkens (2012a), or more directly because it is not seen or 'counted' by university management as a scientific activity.…”
Section: = 330mentioning
confidence: 99%
“…Consequently, if the citation period is extended, the number of uncited publications should decrease, causing the variance in the citations obtained for each publication to increase. Nicolaisen and Frandsen (2019) discovered that the ratio of non-citation frequency of publications reacts sensitively to the length of the citation period. Hu and Wu (2014) found that for a citation period of 12 years or longer, the percentage of papers never cited is stable and the probability of being cited in the future is very low for these publications.…”
Section: Literature Overview and Detailed Research Questionsmentioning
confidence: 99%